Approaches to Thoracic and Lumbar Spine: Our 10 Years Review - Datta, Parthasarahi (International Journal of Scientific Research and Management (IJSRM), 2019)
Background: Lesions of the Thoracic and lumbar spine (TL) are numerous. These lesions affect one or more columns (anterior, middle and posterior) of the spine and compress the spinal cords either from anterior and posterior, giving rise to the features of radiculo-myelopathy. These lesions can be approached either from the anterior or posterior aspect of the spine. We present our last 10 years experience regarding the comparison between two approaches. Methods: Retrospective analysis of records of all patients with thoracic and lumbar lesion treated in our hospital between January 2005 and June 2014 was performed. Over the last 10 years, we came across 186 patients of thoracic and lumbar lesion lesion who were operated either by anterior or posterior approach and were the focus of this study. Follow up ranged from 6 months to 7 years. Results: All the patients presented with neurological deficits. They were evaluated with investigation protocol of our hospital. Anterior approach was done in 38 cases (n = 38) and posterior approach was done in 148 cases (n = 148). We compared between the two groups in terms of perioperative complications, recovery, persisting symptoms and mortality. Conclusion: Complete recovery is better in the posterior approach (74.3%) v/s 52.6%) and morality is more in the anterior approach (7.9% v/s 1.3%). Keywords: Columns, radiculo-myelopathy, thoracic, lumbar